EFFECT OF CHEMICAL TREATMENT ON NATURAL FIBER REINFORCED POLYMER COMPOSITES - Muthu Kumaran A (International Journal of Modern Agriculture, 2021)
Composite materials play a significant role in various engineering applications for the past few decades. Now, present scenario researchers are focused their attention to found the eco friendly material for to replace the conventional/existing harmful material. The natural available material is the most suitable for the present problem but their properties are to be studied for their different applications. In this proposed study the naturally available Ridge gourd (Luffaacutangula) is selected as reinforcement for preparing the composite material. The mechanical properties of the composites are compared by chemically treated and untreated the reinforcement and fabricates the composite specimens by varying the wt%. This paper attempt to focus on the effect of chemical treatment on mechanical properties enhancement of natural fiber reinforced composite. The mechanical behavior of the composites has been investigated by conducting the various tests. The composite specimens are prepared as per the ASTM standard.